Eradication Rate of Helicobacter pylori on the US–Mexico Border Using the Urea Breath Test. Issue 1 (January 2018) - Liu, Roy P.; Romero, Roberta; Sarosiek, Jerzy; Dodoo, Christopher; Dwivedi, Alok K.; Zuckerman, Marc J.
Abstract : Objectives: Helicobacter pylori is prevalent worldwide, especially in Latin America. Triple and quadruple antibiotic therapies have been relatively effective; however, resistance has emerged in recent years. The treatment success rate of these regimens on the border of the United States and Mexico is unknown. Our study attempted to determine eradication rates of two major regimens based on urea breath test (UBT) results in patients previously diagnosed as having H. pylori in a single center in El Paso, Texas, a city on the geographic border with Mexico. Methods: This was a retrospective cohort study of adult patients with H. pylori who underwent UBT after being treated with triple therapy (amoxicillin/clarithromycin/proton pump inhibitor for 14 days), quadruple therapy (tetracycline/metronidazole/bismuth/proton pump inhibitor, usually for 10 days), or both for H. pylori from 2010 to 2015 in a county hospital. Patients were excluded if they did not complete therapy or if their treatment regimen was unknown. The Student t test and the χ 2 test were used to analyze the data. The cumulative incidence and 95% confidence interval (CI) for treatment success were estimated. Results: A total of 104 patients completed the treatment for H. pylori and had UBT. Mean age was 53 years, 76% were women, 85% were Hispanic, and mean body mass index was 30.5 kg/m 2 . Of the 104 patients diagnosed as having H. pylori, 88 received triple therapy (84.6%) and 16 received quadruple therapy: 12 (11.5%) standard quadruple therapy, 4 (3.9%) triple therapy plus metronidazole. There were no differences between groups regarding age, sex, body mass index, or ethnicity. Overall, 90 (86.5%, 95% CI 78–92) patients had negative UBT after initial treatment. Based on posttreatment UBT, the triple therapy group had a similar eradication rate compared with the quadruple therapy group (78/88, 88.6% vs 12/16, 75.0%, P = 0.22). Of the 14 patients with positive posttreatment UBT, 12 (85.7%) received retreatment (2 were lost to follow-up), 11 (91.7%) received quadruple therapy, and 1 (8.3%) received triple therapy. Eradication was successful in 9 of 12 (75%, 95% CI 43–95) patients at retreatment. As such, of the initial 104 patients, 99/104 (95.2%) achieved H. pylori eradication posttreatment (either initial or retreatment). Conclusions: In a predominantly Hispanic population on the US–Mexico border, H. pylori eradication rates based on UBT results were relatively high and were similar for triple therapy and quadruple therapy. Quadruple therapy was effective for those who failed the initial H. pylori treatment. This may have implications for cost-effective therapy in our region. Abstract : Triple and quadruple antibiotic therapies for Helicobacter pylori have been effective, but resistance to therapy has emerged in recent years. The treatment success rate of these regimens on the US–Mexico border is unknown. To determine eradication rates of two major regimens in patients previously diagnosed as having H. pylori in a single center in El Paso, Texas on the border with Mexico, the authors performed a retrospective cohort study of adult patients with H. pylori who underwent a urea breath test after being treated with triple therapy (amoxicillin/clarithromycin/proton pump inhibitor), quadruple therapy (tetracycline/metronidazole/bismuth/proton pump inhibitor), or both. H. pylori eradication rates based on urea breath test results were relatively high and were similar for triple therapy and quadruple therapy (78/88, 88.6% vs 12/16, 75.0%; P = 0.22).